Ritual, Religion, and Reform: The Impact of Khuruj on the Tablighi Jamaat Community - Razak, Yusron; Asrori, Saifudin (Buletin Al-Turas, 2024)
PurposeThis article examined the impact of Khurûj, a ritual practice of the Tablighi Jamaat, on personal transformation and community solidarity. Khurûj, practiced as a form of worship, aims to encourage adherence to Islamic teachings and foster brotherhood among Muslims. This activity served as a means of both self and communal reform, enhancing individual influence within the community and building a sense of belonging and support MethodThrough a qualitative study of the Tablighi Jamaat community in Jakarta, this research highlighted how Khurûj influenced personal development, deepens spiritual experiences, and strengthens communal bonds. Data were collected through semi-structured interviews with members who participated in Khurûj for more than five years, and participatory observation during Khurûj activities. Thematic analysis revealed key themes such as personal transformation, spiritual growth, and enhanced community solidarity Results/findingsThe study underscored the crucial role of ritual interactions in reinforcing social bonds and religious identity among members. Despite perceptions of isolationism, the findings show significant social engagement, including efforts to combat drug use and provide community services, demonstrating a positive contribution to broader society ConclusionThe concludes that Khurûj is valuable for fostering religious adherence and community cohesion, and further research is needed to explore its long-term impacts and influence in different socio-political contexts